2022
DOI: 10.3390/ma15238692
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermophysical and Mechanical Properties of Sandstone Due to High-Temperature

Abstract: In this study, thermophysical and mechanical tests were conducted on sandstone samples from room temperature to 1000 °C. Based on the test results, the thermophysical properties (such as specific heat capacity, thermal conductivity, and thermal expansion coefficient) of sandstone after high-temperature treatment and the variations of mechanical properties (including peak strength, peak strain, elastic modulus, and whole stress-strain curve) with temperature were analyzed. Indeed, the deterioration law of sands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The physical and mechanical behaviour, fracture, damage, and evolution processes of geomaterials under various environmental and mechanical conditions, such as thermal, mechanical, chemical, and electrical environments [6][7][8][9][10][11][12][13][14][15][16][17]20,21].…”
Section: Short Description Of the Articles Presented In This Special ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The physical and mechanical behaviour, fracture, damage, and evolution processes of geomaterials under various environmental and mechanical conditions, such as thermal, mechanical, chemical, and electrical environments [6][7][8][9][10][11][12][13][14][15][16][17]20,21].…”
Section: Short Description Of the Articles Presented In This Special ...mentioning
confidence: 99%
“…Dong et al [21] conducted thermophysical and mechanical experiments on sandstone samples at temperatures ranging from room temperature to 1000 • C. The thermophysical properties of sandstone following a high-temperature treatment and the temperaturedependent changes in mechanical properties were analysed. The results indicate that as the temperature increases, the specific heat capacity and thermal expansion coefficient of sandstone samples subjected to a high-temperature treatment first increase and then diminish, while the thermal conductivity decreases gradually.…”
mentioning
confidence: 99%
“…The change trend with temperature of the uniaxial compressive strength of sandstone can be divided into three types, as shown in Figure 14b: ➀ The uniaxial compressive strength of sandstone at temperatures below 400 °C increases with temperature, and when the temperature rises to 600 °C, the strength of sandstone decreases (as shown in this paper for β = 0° sandstone). ➁ Under heating conditions of 200 °C, the uniaxial compressive strength of sandstone is obviously improved, and the strength gradually decreases with σ relationship between σ c and temperature [33][34][35][36][37][38]; (c) relationship between normalized E and temperature [8,32,37,38].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Figure 14. (a) Relationship between normalized vp and temperature[13,[31][32][33]; (b) normalization σ relationship between σc and temperature[33][34][35][36][37][38]; (c) relationship between normalized E and temperature[8,32,37,38].…”
mentioning
confidence: 99%
“…The majority of research discovered that after being heated to a high temperature, sandstone's peak strength and mechanical properties were dramatically decreased Zhang et al, 2017). (Dong et al, 2022) investigated the changes in physical and mechanical characteristics of sandstone following temperature treatments ranging from ambient temperature to 1000°C. The results revealed that the peak strength of sandstone increased and then fell with rising temperature, the modulus of elasticity decreased, and the peak strain increased at an accelerated pace in the experimental temperature range.…”
Section: Introductionmentioning
confidence: 99%